The Role of Job Motivation and Job Satisfaction in Mediating theEffect of Teacher’s Certification on The Teacher’s Performance in Gorontalo Elementary - Tantawi, Rezkiawan; Armanu, Armanu; Sudjatno, Sudjatno (Jurnal Aplikasi Manajemen, 2016)
This study not only aimedto test Â and analyze the impact of teacher's certification, motivation, and job satisfaction on the teacher's performance, but also to examine and analyze how the role of motivation and job satisfaction in mediating the impact of teacher certification on teacher's performance. The population in this study were 712 certified teachers with a total sample of 233 respondents. Samples were taken using simple random sampling technique. The data obtained from the samples were analyzed using path analysis. The results showed that there was a significant effect of teacher's certification to motivation, job satisfaction, and teacher's performance. Motivation and satisfaction significantly affect the performance of teachers. Motivation and job satisfaction as a partial mediation role in the impact of teacher's certification on teacher's performance, which indicates that the teacher's certification may affect the performance of teachers either with or without the support of their motivation and job satisfaction.